Contemporary NSTEMI management: the role of the hospitalist. Issue 1 (1st January 2020) - Pollack, Charles V; Amin, Alpesh; Wang, Tracy; Deitelzweig, Steven; Cohen, Marc; Slattery, David; Fanikos, John; DiLascia, Christopher; Tuder, Regan; Kaatz, Scott
ABSTRACT: Non-ST-segment elevation myocardial infarction (NSTEMI) is defined as elevated cardiac biomarkers of necrosis in the absence of persistent ST-segment elevation in the setting of anginal symptoms or other acute event. It carries a poorer prognosis than most ST-segment elevation events, owing to the typical comorbidity burden of the older NSTEMI patients as well as diverse etiologies that add complexity to therapeutic decision-making. It may result from an acute atherothrombotic event ('Type 1') or as the result of other causes of mismatch of myocardial oxygen supply and demand ('Type 2'). Regardless of type and other clinical factors, the hospital medicine specialist is increasingly responsible for managing or coordinating the care of these patients. Following published guidelines for risk stratification and basing anti-anginal, anticoagulant, antiplatelet, other pharmacologic therapies, and overall management approach on that individualized patient risk assessment can be expected to result in better short- and long-term clinical outcomes, including near-term readmission and recurrent events. We present here a review of the evidence basis and expert commentary to assist the hospitalist in achieving those improved outcomes in NSTEMI. Given that the Society for Hospital Medicine cites care of patients with acute coronary syndrome as a core competency for hospitalists, it is essential that those specialists stay current on optimal NSTEMI care. Abbreviations : ACC: American college of cardiology; ACCOAST: comparison of prasugrel at the time of diagnosis in patients with non-ST elevation myocardial infarction; ACS: acute coronary syndrome; ADP: adenosine diphosphate; AHA: American heart association; ARB: angiotensin II receptor blocker; ASA: acetylsalicylic acid; CABG: coronary artery bypass graft: CAD: coronary artery disease; CCTA: coronary computed tomography angiography; cTn: cardiac troponin; CRUSADE: can rapid risk stratification of unstable angina patients suppress adverse outcomes with early implementation of the ACC/AHA guidelines; CURE: clopidogrel in unstable angina to prevent recurrent events; CURRENT: OASIS-7 clopidogrel and aspirin optimal dose usage to reduce recurrent events–seventh organization to assess strategies in ischemic syndromes; ECG: electrocardiogram; ED: emergency department; ESRD: endstage renal disease; ESC: European society of cardiology; FDA: food and drug administration; GRACE: global registry of acute coronary events; LVEF: left ventricular ejection fraction; MACE: major adverse cardiac event; MI: myocardial infarction; MVO2 : myocardial oxygen demand; NSTEMI: non-ST-segment-elevation myocardial infarction; NTG: Nitroglycerin; PCI: percutaneous coronary intervention; plato: platelet inhibition and patient outcomes; PPI: proton pump inhibitor; PURSUIT: platelet glycoprotein IIb/IIIa in unstable angina: Receptor Suppression Using Integrilin Therapy; RAAS: Renin-Angiotensin-Aldosterone System; SHM: society of hospital medicine; STEMI: ST-segment-elevation myocardial infarction; TIMI: Thrombolysis in Myocardial Infarction; TRITON-TIMI:trial to assess improvement in therapeutic outcomes by optimizing platelet inhibition with prasugrel—thrombolysis in myocardial infarction